Molecular study of the dentin-pulp complex responses to caries progression - Yani Corvianindya Rahayu (Dental Journal (Majalah Kedokteran Gigi), 2007)
The dentin-pulp complex exhibits various responses to caries, including events of injury, defense, and repair. The overall responses dependent on pulp cell activity and the signaling processes, which regulate the behavior of these cells. The signals for tissue repair are thought to be mediated by dentin-bound growth factors released during caries progression. Growth factors are a key of molecules responsible for signaling a variety of cellular process following dental injury. The endogenous proteolytic enzymes (Matrix metalloproteinases, MMPs) present in dentin matrix might also participate in releasing bioactive molecule. Several members of the MMP family are found in the soft and hard tissue compartment of dentin-pulp complex. Their presumed role in many physiological process during the development and maintenance of the dentin-pulp complex, they may also contribute to the pathogenesis of dentin caries and the responses elicited by caries.